Ag/AgI nanoparticles decorated WO3/TiO2 nanotubes with enhanced visible light photocatalytic activity - Li, Tingting; Luo, Shenglian; Luo, Yan; Yang, Lixia (Materials letters, 2016)
A composite photocatalyst, Ag/AgI nanoparticles decorated WO3 pre-dopedTiO2 nanotube arrays, were constructed, which showed enhanced catalytic activity induced by the visible light. The composite structure was fabricated by a three-step method, including electrochemical anodization, wet impregnation and photo-assisted reduction. The as-prepared materials were characterized by X-ray diffraction, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, transmission electron microscopy and ultraviolet-visible (UV–vis) diffuse reflectance spectroscopy. The results revealed that the absorption range of the TiO2 nanotubes (TNTs) could be extended from ultraviolet to visible light range after the deposition of WO3 species and Ag/AgI nanoparticles. Compared with the TNTs, WO3/TNTs and Ag/AgI−TNTs, the WO3/TNTs decorated with Ag/AgI(Ag/AgI/WO3@TNTs) showed much higher photocatalytic activity in the degradation of hydroquinone under visible light (λ≥420nm) irradiation. [Display omitted] •Ag/AgI/WO3@TNTs catalyst with novel structure was facilely constructed.•The resulting catalyst is sensitive to the visible light.•The resulting catalyst exhibits superior activity in photocatalytic degradation of hydroquinone.